PENERAPAN SCAFFOLDING LEARNING BERBASIS KARAKTER DALAM MENINGKATAN HASIL BELAJAR MATERI EKSPONEN DAN LOGARITMA KELAS X.1 PADA SEMESTER 1 SMAN 1 TANJUNG TAHUN PELAJARAN 2014/2015 - winarno winarno (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2017)
The objective of this research is to improve the learning outcomes of Exponential and Logarithmic through character-based scaffolding learning of class X.1 of SMA Negeri 1 Tanjung Semester 1 in the academic year of 2014/2015. The learning outcomes in this research include three aspects, (1) affective, sel-reliance characters variables; (2) psychomotoric, problem solving skills variables; and (3) cognitive, studentsâ€™ learning achievement. The primary and secondary data were used in this research.The data were gained from technique test in the form of essay test and non-test technique in the form of studentsâ€™ sel-reliance characters and problem solving skills observation. The descriptive comparative analysis is used to compare the result of the pre-test and the post-test score with the key performance indicator 85%. The result of analysis showed that the learning result with the Minimum Mastery Criteria of 75 at the pre-test was 51,28% from 39 students. Result of Cycle I was 64,10% for self-reliance character, 53,85% for problem solving skill, and 61,54% learning achievement. Cycle II was 89.75%, 87.18%, and 87.18%. The increasing of self-reliance character 25.65%, problem solving skills 33.33%, and learning achievement 25.64%.Â Keywords: scaffolding, self-reliance character, problem solving skills